2021
DOI: 10.3389/fgene.2021.616507
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtypes Based on the Stemness Index Predict Prognosis in Glioma Patients

Abstract: Glioma is the common histological subtype of malignancy in the central nervous system, with high morbidity and mortality. Glioma cancer stem cells (CSCs) play essential roles in tumor recurrence and treatment resistance. Thus, exploring the stem cell-related genes and subtypes in glioma is important. In this study, we collected the RNA-sequencing (RNA-seq) data and clinical information of glioma patients from The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databases. With the differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Shiokawa et al also demonstrated that the slow-cycling subpopulation of CSCs was rather significant in COAD development and chemoresistance [13]. Recently, a novel caner stemness index (named mRNAsi), which was developed by deep learning methods [14], has been extensively researched in various types of cancer, including bladder cancer [15], gastric carcinoma [16], lung cancer [17], and glioma [18]. However, there was not an integrated investigation of COAD stemness features using high-throughput data.…”
Section: Introductionmentioning
confidence: 99%
“…Shiokawa et al also demonstrated that the slow-cycling subpopulation of CSCs was rather significant in COAD development and chemoresistance [13]. Recently, a novel caner stemness index (named mRNAsi), which was developed by deep learning methods [14], has been extensively researched in various types of cancer, including bladder cancer [15], gastric carcinoma [16], lung cancer [17], and glioma [18]. However, there was not an integrated investigation of COAD stemness features using high-throughput data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stemness phenotype can exhibit a particular molecular signature. Malta et al (2018) took advantage of this profile and proposed the OCLR algorithm that can be applied to determine a stemness index in different cells and tissues in addition to being able to reveal the stemness levels in different human cancers such as lung cancer (Liao et al, 2020;Zhang et al, 2020), bladder cancer (Pan et al, 2019), medulloblastoma (Lian et al, 2019), breast cancer (Pei et al, 2020), and glioma (Tan et al, 2021). In this study, we showed that mRNAsi can also be determined in canine species correlating to stemness features.…”
Section: Discussionmentioning
confidence: 76%
“…MC1 showed the highest proliferation score, followed by MC2 and MC3 ( Supplementary Figure S3D ). Studies have demonstrated that LGG patients with higher mRNAsi indices have a better prognosis than those with low mRNAsi indices ( Tan et al, 2021 ) ( Supplementary Figure S3E ). We obtained and analyzed mRNAsi differences in LGG patients from our data, and found that the mRNAsi indices of MC2 and MC3 were significantly higher than that of MC1.…”
Section: Resultsmentioning
confidence: 99%